Computational approach for membrane desalination system development - Mo, Zijing (Nanyang Technological University, 2024)
Along with surging population growth, the rapid pace of urbanization and industrialization were observed in many developing economies, resulting in a burst in water demand. As predicted by the World Bank Group, by 2030, the world would face a 30% of water shortage if the current trend on demand and supply-side remain unchanged. Therefore, an increased amount of resources should be devoted to the strategic options that can close the gap between water supply and demand. While RO is the most viable solution to closing such gap, it remains energy intensive which hurdle its wide application. The primary objective of this study is to improve energy efficiency in reverse osmosis (RO) designs for desalination, focusing on economically feasible solutions. Despite advancements in alternative RO designs, concerns persist, hindering their widespread adoption. This study addresses these concerns and knowledge gaps to optimize RO system configurations and reduce energy consumption.